Face. Off. Faceoff: Mapping African Representations in Western Art Institutions - (:unkn) unknown (My University, 2019)
In this project, I analyze the influential perceptions of African art objects, cultures, and histories formed through audience interactions with museum representations of Africa. In the Western world, curiosity cabinets and natural history museums first presented African objects as cultural artifacts aimed to intrigue and educate viewers about distant, exotic lands. Later, art museums reclassified African objects as art and some displays highlighted this shift, but African art exhibitions largely conformed to the anthropological models previously established. Scholars have analyzed these distinct display techniques while considering the visual environment from which these works were historically significant. Despite this critical scholarship, institutional presentations of permanent African art collections remain stagnant and hierarchical. Building on this research, I consider the various display techniques implemented Chazen Museum of Art, Madison, The Art Institute of Chicago, Yale University Art Gallery, Museum of Fine Arts, Houston, and The Menil Collection to inform my own installation of African objects in a gallery setting. Through the catalogue and exhibition, I investigate how influential representations of African art objects, cultures, and histories within Western art museums impact contemporary museum audiences. African artworks, installed in two distinct types of displays, demonstrate the constructed and mediated nature of museum exhibits. This two-part exhibition highlights the need for transparency within museum installations, encouraging visitors to question the selection of objects shown, how these objects are staged for viewing, and what type of information frames this viewing.
Keywords: Aesthetic art display; African art; Anthropological art display; Art hierarchy; Art installation transparency; Museum critique